До бріофлори Регіонального ландшафтного парку “Гранітно-степове Побужжя” - ПАРТИКА, ЛАРИСА ЯКІВНА; ВІРЧЕНКО, ВІТАЛІЙ МИХАЙЛОВИЧ; НИПОРКО, СВІТЛАНА ОЛЕКСІЇВНА (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
До бріофлори Регіонального ландшафтного парку “Гранітно-степове Побужжя”